Partial substitution of rice husks for manure in greenhouse vegetable fields: Insight from soil carbon stock and aggregate stability. (6th July 2021) - Fei, Chao; Zhang, Shirong; Li, Junliang; Liang, Bin; Ding, Xiaodong
Abstract: Soil aggregate stability and C stock are key factors in greenhouse vegetable production, which are influenced by the application of different organic materials. However, the responses of soil aggregate stability and C stock to organic amendment in greenhouse vegetable fields are not well understood. A 5‐year study was carried out in greenhouse vegetable fields to investigate the effect of partial substitution of rice husks for manure on soil aggregate stability, C compositions, and their relationships. Four treatments included: (a) no organic fertilization (control), (b) 30 t ha −1 chicken manure (CM), (c) 30 t ha −1 rice husks (RH), and (d) 10 t ha −1 chicken manure plus 20 t ha −1 rice husks (MR). Rice husks addition significantly increased the proportion of >2 mm aggregates and mean weight diameter (MWD), while manure addition showed no difference with control. Polysaccharide and humin (HM) were increased with rice husks addition (RH and MR) compared with that in CM treatment. Polysaccharide and HM caused 86.03% variation of soil aggregate, in which polysaccharide and HM contributed 76.3 and 9.7%, respectively. The soil C stock in CM, RH, and MR treatments was increased by 146, 175, and 164% compared with control, respectively. Aliphatic‐C and amorphous Fe‐oxides (Fe‐ox) content were as higher in MR added soil than those in RH treatment. Partial substitution of rice husk for manure improved soil aggregation stability and thus enhanced C stock by suppling more polysaccharide, HM and liberated soil minerals, which was conducive to the sustainable development in greenhouse vegetable production.